Closing pandora's box: How to improve the common reporting standard - Menusch Khadjavi; Marjolein Vertelman (Kiel Institute for the World Economy (IfW Kiel), 2022)
The 2021 pandora papers show that many wealthy individuals and even politicians use shell companies to hide their fortunes. In order to fight international personal tax evasion, the Common Reporting Standard (CRS) was implemented and it helped governments to collect USD 85 billion already. USD 182 billion are still missing from the government budget because of personal tax evasion. The individual implementation strategies of CRS compliant countries can endanger the effectiveness of the Automatic Exchange of Information (AEOI). Several loopholes are used to circumvent the CRS. There are amendments possible which increase the effectiveness by improving the implementation strategies and closing the loopholes. The enforcement of the CRS should become stricter by removing financial institutions' licenses to operate in cases of non-compliance. Beneficial ownership registers should increase transparency regarding investments and securities. Within the current momentum of international tax legislation, the CRS compliant countries may leverage the USA into signing the CRS as well. The USA could in turn demand a more effective CRS before signing it.
Keywords: H20; H26; 330; Common Reporting Standard (CRS); Automatic Exchange of Information (AEOI); global taxevasion; improvements; loopholes